The Relationship Between Fundamental Factors and Stock Return: A Case Based Approach On Banking Companies Listed In Indonesia Stock Exchange - Abdulmannan, Adamilyara Aqil; Faturohman, Taufik (Journal of Business and Management, 2015)
Abstract: This study investigates the relationship of various fundamental factors in determining the stock price in Indonesia Stock Exchange (IDX). It consists of 22 listed banking companies under banking sub-sector in Indonesia Stock Exchange (IDX). This aim of this study is to figure out the relationship between stock price and companies performance, which include earning per shares (EPS), dividend per shares (DPS), fixed assets to total assets (FA/TA), return on assets (ROA), and return on equity (ROE) towards long term stock price changes. This paper is using annual data that gathered from company’s financial annual report from 2005 to 2013. This study focused on the banking sub-sectors listed in Indonesia Stock Exchange. This study uses multiple regression analysis as a method for deeper understanding and analysis. This research found that there are not statistically significant relationship between chosen fundamental factors toward stock return. This study also expected to contributes for helping the investor in investing their valuable assets to stock market especially in banking sector. This research is quite interesting due to the topic research in Indonesia’s context. Keywords: Indonesia Stock Exchange, Stock Return, Fundamental Factors, Multiple Regression